(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The aim of this contribution is to analyse five unpublished wills of three exiles of the Visconti family – Carlo, Mastino and Drusiana – heirs of the Lord of Milan Bernabò, forced to flee after the coup in 1385 by Gian Galeazzo Visconti. Drawn up in Venice according to the meticulous local notarial practice, the sources offer a privileged insight into the management of the estate, the dynastic strategies and the roots in the Serenissima, which had become their new social and economic centre. The analysis reveals the use of the testamentary bequest as a political instrument and for consolidating family memory: the practices of heritage protection are intertwined with the desire to integrate into the institutional and financial circuits of Venice, whose city institutions assume a key role. What emerges is a profound transformation of wills, which marks the passage from dynastic ambition to the construction of a new urban identity, centred on the conservation of the Visconti prestige and on the decisive weight of the hereditary estate, testifying to the ways in which the nobility in exile acted in the late Middle Ages.